The Adobe Photoshop CS5 book for digital photographers - Kelby, Scott ([Berkeley, Calif.] : New Riders, 2011)
Kelby shows you exactly step by step the exact techniques used by today's cutting-edge digital photographers.
Mini series : using Photoshop CS5's mini bridge -- WWF raw : the essentials of Camera Raw -- Raw justice : Camera Raw : beyond the basics -- Attitude adjustment : Camera Raw's adjustment tools -- Scream of the crop : how to resize and crop photos -- Jonas sees in color : color correction secrets -- Black & white : how to create stunning B&W images -- We are HDR : creating HDR images -- Little problems : fixing common problems -- Side effects : special effects for photographers -- Sharpen your teeth : sharpening techniques -- Fine print : step-by-step printing and color management -- Workflow : my step-by-step workflow.
Includes index.
Keywords: Adobe Photoshop; Photography -- Digital techniques; Computer graphics -- Computer programs; Image processing -- Digital techniques